Antibacterial activity of garlic ethanol extract (Allium sativum Linn) against Propionibacterium acnes - Stefania Danita Dwi W. M. Seran; Rr. Listyawati Nurina; Regina Marvina Hutasoit; Teguh Dwi Nugroho (Acta Biochimica Indonesiana, 2025)
Background: Acne vulgaris is a common dermatological condition largely associated with Propionibacterium acnes infection. The increasing resistance of P. acnes to conventional antibiotics necessitates alternative treatment approaches. Garlic (Allium sativum Linn) has documented antimicrobial properties, yet its specific activity against P. acnes remains underexplored. Objective: To evaluate the antibacterial activity of garlic extract at various concentrations against P. acnes and determine its potential as an alternative acne treatment. Methods: Garlic extract was prepared using ethanol maceration, followed by phytochemical screening. The antibacterial activity against P. acnes was assessed using the well diffusion method at concentrations of 10%, 40%, 70%, and 100%, with doxycycline and distilled water serving as positive and negative controls, respectively. Inhibition zones were measured and statistically analyzed. Results: Phytochemical screening revealed the presence of tannins, flavonoids, alkaloids, saponins, and triterpenoids in the garlic extract. All tested concentrations exhibited significant antibacterial activity against P. acnes. The inhibition zone diameters were 32.83 mm (100%), 28.90 mm (70%), 26.60 mm (40%), and 15.29 mm (10%), compared to 38.81 mm for doxycycline, with statistically significant differences between all groups (p<0.05). Conclusion: Garlic extract demonstrates potent antibacterial activity against P. acnes, with 70% concentration providing optimal efficacy relative to extract concentration, suggesting its potential as a natural alternative for acne treatment.